(untitled) (Jurnal Bahasa, 2018)
This article discusses linguistic politeness in Melunas Rindu, a text in the literature component (Komsas) for Form 4 students in Zone 4 (Johor, Sabah, Sarawak and the Federal Territory of Labuan). Politeness is an essential aspect in life and it is a socio-cultural element in society. The dialogue of the main and supporting characters in Chapter 5 of this novel was analysed. The politeness models of Grice and Leech were applied in the analysis. Both models present maxims of politeness which have to be observed in order to create conflict-free situations. The methodology employed in this research includes library research, text analysis and quantitative analysis. Based on the classifications and the analysis, the findings show only four out of six of Leech’s maxims, and two out of four of Grice’s are observed. This study revealswhich are the dominant forms of linguistic politeness (according to the models of Grice and Leech) found in this novel, that at once also reflect Malay socio-culture. Keywords: Komsas, politeness principle, co-operative principle, socio-culture, pattern of maxims, combinations of maxims, tact maxim, lexical